2016
DOI: 10.1021/acs.organomet.5b00967
|View full text |Cite
|
Sign up to set email alerts
|

Transfer Hydrogenation of Nitriles, Olefins, and N-Heterocycles Catalyzed by an N-Heterocyclic Carbene-Supported Half-Sandwich Complex of Ruthenium

Abstract: In the presence of KOBut, N-heterocyclic carbene-supported half-sandwich complex [Cp­(IPr)­Ru­(pyr)2]­[PF6] (3) (IPr = 1,3-bis­(2,6-diisopropylphenyl)­imidazol-2-ylidene) catalyzes transfer hydrogenation (TH) of nitriles, activated N-heterocycles, olefins, and conjugated olefins in isopropanol at the catalyst loading of 0.5%. The TH of nitriles leads to imines, produced as a result of coupling of the initially formed amines with acetone (produced from isopropanol), and showed good chemoselectivity. Reduction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 75 publications
0
54
0
1
Order By: Relevance
“…Beller and co-workers demonstrated that Ru(II)-1,4-bis(diphenylphosphino)butane catalyzed TH of aromatic and aliphatic nitriles to amines in 2-butanol at 120°C. 47,48 Both complexes showed excellent catalytic activity but the catalyst loading were relatively high. 46 Reductive amination of the primary amine with acetone, generated from nitrile and 2-propanol respectively during TH, produced the secondary amine.…”
Section: Introductionmentioning
confidence: 99%
“…Beller and co-workers demonstrated that Ru(II)-1,4-bis(diphenylphosphino)butane catalyzed TH of aromatic and aliphatic nitriles to amines in 2-butanol at 120°C. 47,48 Both complexes showed excellent catalytic activity but the catalyst loading were relatively high. 46 Reductive amination of the primary amine with acetone, generated from nitrile and 2-propanol respectively during TH, produced the secondary amine.…”
Section: Introductionmentioning
confidence: 99%
“…Despite a higher load of 5 mol %, they are still outperformed by catalysts 1–6 . Neutral tris(hydride) species 10 and 11 (entries 10 and 11), which were identified as resting states in our previous transfer hydrogenation studies,, are more active than 7–9 but their activity is also inferior to their precursors 1 and 3 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, 4‐cyano‐pyridine remained untouched under these catalytic conditions (entry 9). Attempted reduction of aliphatic nitriles resulted in only moderate to good yields (entries 11–14), which agrees well with the results of our previous studies ,. Noteworthy, a nitrile bearing an alkynyl group was reduced selectively at the C≡N bond (entry 13).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations